Pelanggaran Privasi dan Ancaman Terhadap Keamanan Manusia dalam Kasus Cambridge Analytica - Faris Azhar Zaelany; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2023)
Cambridge Analityca is a data-based political consulting firm that intervened in the US elections (2016) using the OCEAN method to attract voters. The problem here is the data obtained using illegal methods through quizzes and advertisements on Facebook. With the data obtained by Cambridge Analityca, they can use this data for the benefit of their companies and their clients, thereby endangering the targeted citizens. This research wants to explain how the violation cause by Cambridge Analityca become a threat. In answering this question, the concept of Human Security and cybersecurity is used. This study uses an descriptive method in answering the problem. The results of this study found that the threat posed by this case harmed not only citizens but the state and also the violations that occur can cause a collapse in security and social life.